A simple, solvent free method for transforming bio-derived aldehydes into cyclic acetals for renewable diesel fuels. Issue 12 (15th October 2018) - Staples, Orion; Moore, Cameron M.; Leal, Juan H.; Semelsberger, Troy A.; McEnally, Charles S.; Pfefferle, Lisa D.; Sutton, Andrew D.
Abstract : The acetalization of 2, 3-butanediol with bio-derived C4–8 aldehydes has yielded a route to substituted 1, 3-dioxolanes from small bio-building blocks. Abstract : The acetalization of 2, 3-butanediol with bio-derived C4–8 aldehydes has yielded a route to substituted 1, 3-dioxolanes from small bio-building blocks. The reported reaction system features excellent carbon yields (>93%), atom economy (>89%) and phase separation of the analytically pure product which eliminates elaborate purification processes and facilitates simple catalyst recycling. The 1, 3-dioxolanes offer performance advantages over traditional diesel and have the potential to augment petroleum derived fuels.